Colorectal Cancer Screening Program - Montano, Daniel; Fenocchi, Eduardo; Martínez, Luz; Tolve, Julio; Rondán, Mariella (Cirugía del Uruguay, 2005)
Colo- Rectal cancer constítutes a national health prob/em and in view of this our group has deve/oped a Screening program for ear/y detection and teatment of this patho/ogy The purpose of this paper is to evaluate cases in which this methodology was applied, thus validating the practicity and acceptability of massive detection techniques. lt is with this aim in view that we have integrated immunologic diagnosis of occult blood in faeces and whenever the results proved positive we proceeded to conduct a videoendoscopic and histological diagnosis. Acceptance has been considerable (90. 1 % ) and we have positive index of 11. 1 %. Once patho/ogies detected through endoscopy was analyzed, we found a high predominance of neop/asic /esions. We diagnosed 101 cancers, 47 of which were early detections while 54 had reached an advanced stage. We a/so found 237 adenomas